VIBRATION SIGNAL ANALYSIS OF A MOTORCYCLE - Suphattharachai Chomphan (GEOMATE Journal, 2019)
Nowadays, the motorcycle is becoming widely popular because of their swiftness and conveniences in crowded cities. It is considered the most popular choice in various aspects of transportation in the urban area. When starting and accelerating the engine, it has been found that there was a vibration throughout all parts of the motorcycle. If the driver perceives more vibration, he will feel more uncomfortable. Consequently, the researcher conducted a study of the vibration signal sent through four core points which are the contacts between driver or rider and the motorcycle body including motorcycle left hand, seat, left front footrest, and left rear footrest. The specimen motorcycle is Honda Wave 100s model. The comparison results have been performed by using two parameters of averaged peak and averaged energy of the vibrational signal. The results reveal that the left front footrest has the highest vibration level in both parameters, while the seat has the lowest vibration level. Last but not least, it can be concluded that the mechanical structure of the motorcycle must be developed by considering the engine’s vibration sent through all parts especially the position of front footrest which has the highest impact in order to increase the driver’s comfort at the highest satisfaction.